The truth of the dispute in five issues of fairness (Journal of the College of Basic Education, 2023)
The grammatical dispute began early with the emergence of Arabic grammar, especially when extracting phenomenagrammar and its complexity, a dispute developed between the grammarians of the two schools of Kufa and Basra, as well asThe scholars of the same school, and the reason goes back to the method of collecting the language and taking from the Arabs.The Basrans took the language from the plains of Najd, the Hijaz, and Tihama, while the Kufans took it from theThe Arab tribes and the Basrans interpret the linguistic phenomena in the Holy Qur’an in the most eloquent languages.The Arabs count that which cannot be compared to what is heard and memorized and not measured against it, whileThe Kufans hear the language more than they measure, especially their sheikh Al-Kisa’i. Then there is a discrepancy inThe ability to deduce between the scholars of the two schools and the scholars of the same school, all of this led toto the emergence of grammatical differences that developed the grammar lesson in the light of compromising and crowdingscientific.